PAIR-LIST READING DALAM INDONESIA- INGGRIS INTERLANGUAGE - Ariviani Dewi, Eny Kustiyah (MAJALAH ILMIAH GEMA, 2014)
This research aims at revealing the existence of interlanguage in the secondlanguage learning process and desccribing the sources of interlanguage. The methodof the research is descriptive qualitative. The objects of the research are derivedfrom the abstract of scientific journals in Paradigma Vol.04 No.01 February-July2010 and Serambi Hukum Vol.02 No. 02a February-July 2008. The presentresearcher employs library research and note-taking technique to collect the data.Selinker’s Interlanguage is the theoretical approach in this research. The outcome ofthe research is as follows: (1) the existence of interlanguage found in the abstract ofUNIBA’s scientific journals; (2) the sources on interlanguage are derived fromlanguage transfer, overgeneralization and simplification.Key words: interlanguage, language transfer, overgeneralization, simplification